2013
DOI: 10.1097/igc.0b013e3182a6171a
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Validation of the IOTA Logistic Regression Models (LR1 and LR2) in Comparison to Subjective Pattern Recognition for the Diagnosis of Ovarian Cancer

Abstract: The AUC of the IOTA LR1 and LR2 were similar in nonexpert's hands when compared to the original and validation IOTA studies. The PR method was the more accurate test to diagnose ovarian cancer than either of the IOTA models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
(11 reference statements)
1
10
0
2
Order By: Relevance
“…Our results showed that two experienced sonologists agreed quite well in their classification of masses as benign or malignant using the 10% risk of malignancy cutoff of LR1 and LR2, and that the diagnostic performance of LR1 and LR2 with regard to discrimination between benign and malignant tumors was similar for the two sonologists and similar to that reported by others (14,(26)(27)(28). This is reassuring, because the main purpose of using model LR1 and LR2 is to classify tumors as benign or malignant.…”
Section: Discussionsupporting
confidence: 85%
“…Our results showed that two experienced sonologists agreed quite well in their classification of masses as benign or malignant using the 10% risk of malignancy cutoff of LR1 and LR2, and that the diagnostic performance of LR1 and LR2 with regard to discrimination between benign and malignant tumors was similar for the two sonologists and similar to that reported by others (14,(26)(27)(28). This is reassuring, because the main purpose of using model LR1 and LR2 is to classify tumors as benign or malignant.…”
Section: Discussionsupporting
confidence: 85%
“…This may explain why the results of IOTA phase 3 confirm those of previous IOTA studies that showed excellent test performance of all IOTA strategies (Timmerman et al , 2005, 2007, 2008, 2010a, 2010b; Van Holsbeke et al , 2009, 2012; Ameye et al , 2012; Kaijser et al , 2013; Sayasneh et al , 2013a, 2013b). On the other hand, validation studies of LR1, LR2 and SRs performed outside IOTA studies reported similar results (Hartman et al , 2012; Nunes et al , 2012, 2013; Alcázar et al , 2013), and there is now evidence that the IOTA strategies retain their performance in the hands of sonographers and relatively inexperienced doctors (Hartman et al , 2012; Nunes et al , 2012, 2013; Alcázar et al , 2013; Sayasneh et al , 2013a, 2013b). …”
Section: Discussionmentioning
confidence: 80%
“…Unfortunately, most gynaecologists, radiologists and sonographers have limited experience with the use of SA of ultrasound images to discriminate between benign and malignant adnexal masses. As SRs, SDs and LR2 have been shown to perform very well in the hands of both sonographers and gynaecologists with limited ultrasound experience (Hartman et al , 2012; Nunes et al , 2012, 2013; Alcázar et al , 2013; Sayasneh et al , 2013a, 2013b), they could be used as first stage tests, and patients with inconclusive or equivocal results of the first stage test could be referred for SA by an experienced ultrasound examiner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] An advantage of the LR2 or Simple Rules models over subjective assessment is their objectivity and simplicity, which facilitates their use by ultrasonographers with different backgrounds and various levels of experience. [5, 6]. The vascularity of the mass and the tumour malignant feature M4 was assessed based on some other scans that were not presented in the article.…”
mentioning
confidence: 99%